2006
DOI: 10.1103/physrevlett.97.076805
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Force Microscopy on Oriented Graphite Surfaces: Coexistence of Insulating and Conducting Behaviors

Abstract: We present measurements of the electric potential fluctuations on the surface of highly oriented pyrolytic graphite using electrostatic force and atomic force microscopy.Micrometric domain-like potential distributions are observed even when the sample is grounded. Such potential distributions are unexpected given the good metallic conductivity of graphite because the surface should be an equipotential. Our results indicate the coexistence of regions with metallic and insulating behaviors showing large potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…It has recently been demonstrated that in HOPG samples, regions with "metaliclike" and "insulatinglike" behaviors coexist and the internal structure of bulk HOPG samples is not homogeneous in the micrometer range. 17 This find suggests that HOPG samples may have to be considered as composite materials. In carbon-composite materials, apparent negative resistance has been measured by four terminal technique, which has been explained by the backflow of electrons in the unexpected direction relative to the applied voltage gradient.…”
Section: Fig 3 (A)mentioning
confidence: 99%
“…It has recently been demonstrated that in HOPG samples, regions with "metaliclike" and "insulatinglike" behaviors coexist and the internal structure of bulk HOPG samples is not homogeneous in the micrometer range. 17 This find suggests that HOPG samples may have to be considered as composite materials. In carbon-composite materials, apparent negative resistance has been measured by four terminal technique, which has been explained by the backflow of electrons in the unexpected direction relative to the applied voltage gradient.…”
Section: Fig 3 (A)mentioning
confidence: 99%
“…EFS is performed at well-defined stationary points by sweeping V probe (i.e., −3 to +3 V) with mV resolution, while recording the corresponding phase change Δφ [18,20,113]. The V 2 term in Equation (1) leads to a parabolic response as a result of attractive and repulsive nature of separated charges (Figure 14a).…”
Section: Electrostatic Force Spectroscopy (Efs)mentioning
confidence: 99%
“…on the nanoscale. While the EFM method allows mainly qualitative mapping of the surface potential [7,[18][19][20], the KPFM technique provides quantitative values for the work function difference, Φ s = Φ probe -eV CPD , where Φ s and Φ probe are work functions of the surface and probe, respectively, and V CPD is the contact potential difference directly measured by KPFM. Using KPFM method, both exfoliated [21] and epitaxial [22][23][24] graphene with different number of layers has been studied by various groups.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] However, surface probing techniques capable of atomic resolution make studying surface defects relatively easier. Using scanning tunneling microscopy, [12][13][14][15][16] scanning tunneling spectroscopy, 17,28 atomic force microscopy, 15,29 electrostatic force microscopy, 30 magnetic forces microscopy, 10,11,31 and transmission electron microscopy 9,32 one can visualize both the formation and evolution of defects populations on the surface of graphite [10][11][12][13]15,16,[29][30][31] and related nanostructures. 9 As a result, the generation of single vacancies ͑V͒, 13,16,21,28,[33][34][35][36][37][38][39] multivacancies, 16,21 interstitials ͑I͒, 21,33,35,36,40,…”
Section: Introductionmentioning
confidence: 99%